Analysis of Sustainable Water Resources: A Review of Inter- Sectoral Water Problems and Environmental Hazards (Indian Journal of Forensic Medicine & Toxicology, 2021)
The Water resources Conservation Program is one part of environmental preservation in which is nowimplemented by the Government. Buy the Law Number 17 of 2019 on Water Resources. The regulation inthe context of its implementation is faced with aspects of legal awareness and legal compliance of all partieswho are often unaware of the significance of the water in life. The research result shows an irony whileunderstood that water conservation activities is a responsibility of some parties only. Many breakthroughs canbe used to maintain the environment preservation as a norm, implementation of the principle of participation,especially in the industrial area so that the sustainability of the environment system is maintained to maintainthe ideals of sustainable development and reduce the environmental hazard. One of the solutions offeredis based on the values of human resources concept, which is the foundation of the environmental law byadhering to the principle of participation in sustainable development.